Primary Lymphoma of Bone Presenting as Spindle Cell Neoplasm of the Vertebral Body: A Case Report and Review of the Literature - Mahakit Inklab; Richard H. Steingart; Jonathan K. Freeman (Case Reports in Hematology)
Spindle cell variant of lymphoma is a very rare but known disease entity that can mimic a sarcoma. Diagnosis can be even more challenging if the only site of the disease is in the bone. We report a case of primary lymphoma of bone with spindle cell morphology which was successfully treated with a combination of surgery, chemotherapy, and radiotherapy.